One summer [compact disc, unabridged] : America, 1927 - Bryson, Bill (Random House, Inc., 2013)
One of the most admired nonfiction writers of our time retells the story of one truly fabulous year in the life of his native country; a fascinating and gripping narrative featuring such outsized American heroes as Charles Lindbergh, Babe Ruth, and yes Herbert Hoover, and a gallery of criminals (Al Capone), eccentrics (Shipwreck Kelly), and close-mouthed politicians (Calvin Coolidge).